Recent Progress of Nano-drug Delivery System for Liver Cancer Treatment - Zhou, Feilong; Teng, Fangfang; Deng, Peizong; Meng, Ning; Song, Zhimei; Feng, Runliang (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Liver cancer is one of serious diseases which threaten human life and health. Studies on the treatment of liver cancer have attracted widespread attention. Application of nano-drug delivery system (NDDS) can not only improve selective drug delivery to liver tissue and improve the bioavailability of drug, but also can reduce the side effects of drugs when it is specially modified in the respects of structure modification or specific target molecules decoration. This review will address the latest development of liver-targeted drug delivery system.
Keywords: passive targeting